Genome-wide identification and analysis of the invertase gene family in tobacco (Nicotiana tabacum) reveals NtNINV10 participating the sugar metabolism - Cheng, Lingtong; Jin, Jingjing; He, Xinxi; Luo, Zhaopeng; Wang, Zhong; Yang, Jun; Xu, Xin (Frontiers in Plant Science, 2023)
Sucrose (Suc) is directly associated with plants tolerance to multiple stresses as well as plant growth and development. Invertase (INV) enzymes irreversibly catalyze Suc degradation to produce glucose (Glc) and fructose (Frc). However, genome-wide identification and function of individual members of the INV gene family in Nicotiana tabacum have not been conducted. In this report, 36 non-redundant NtINV family members were identified in Nicotiana tabacum including 20 alkaline/neutral INV genes (NtNINV1-20), 4 vacuolar INV genes (NtVINV1-4), and 12 cell wall INV isoforms (NtCWINV1-12). A comprehensive analysis based on the biochemical characteristics, the chromosomal location, the exon-intron structures and the evolutionary relationships revealed the conservation and the divergence of NtINVs. Segmental duplication and purifying selection were the main factors of NtINV gene evolution. Our analyses also suggested that NtINVs could be regulated by miRNAs, and cis-acting regulatory elements of transcription factors implicated in various biotic and abiotic stress response. In addition, 3D structure analysis has provided evidence for the differentiation between the NINV and VINV. The expression patterns in diverse tissues and under various stresses were investigated, and qRT-PCR experiments were conducted to confirm the expression patterns. Notably, NtNINV10 was up-regulated under drought and salinity stresses, and the NtNINV10-GFP fusion protein was located in the cell membrane. Furthermore, inhibition of the expression of NtNINV10 gene decreased the glucose and fructose in tobacco leaves. Overall, we have identified possible NtINV genes functioned in the processes of leaf development and resistance to environmental stresses in tobacco. These findings contribute to a better understanding of the NtINV gene family and establish the basis for future research.